Targeting tau: Clinical trials and novel therapeutic approaches. (13th July 2020) - VandeVrede, Lawren; Boxer, Adam L.; Polydoro, Manuela
Highlights: Therapeutics that target specific pathology to slow or arrest disease progression are urgently needed in neurodegenerative disease. Tau pathology correlates better with cognitive impairment than Aβ, thus tau-targeted therapeutics may be a more effective. Tau-targeted therapies aim to either ameliorate gain of toxic function from harmful aggregates or replace loss of tau function. This article reviews 24 tau-targeted therapies tested in clinical trials with 16 agents currently in active development. Abstract: Tauopathies are a group of over 20 clinicopathological neurodegenerative diseases including Alzheimer's disease (AD), the most common type of dementia, progressive supranuclear palsy, Pick's disease, corticobasal degeneration, among others. Tauopathies are defined by neurodegeneration and the presence of tau aggregates in affected brains regions. Interestingly, regional tau aggregation burden correlates with clinical phenotype and predicts cognitive status. Autosomal dominant mutations in the MAPT gene lead to tau deposition and clinical FTD syndromes with cognitive, behavioral, and motor impairment. Polymorphisms in or around the MAPT gene have also been strongly linked to other proteinopathies including synucleinopathies. Taken together these findings suggests that tau plays a critical role in neurodegeneration and proteinopathies, supporting the idea that tau targeted approaches can be disease-modifying and lead to clinically meaningful benefits in slowing or reversing disease progression. Increasingly, human clinical trials are testing this hypothesis. This article reviews tau-targeted therapies tested in clinical trials as well as agents currently in active development based on publicly disclosed information. We describe the therapeutic approaches of these trials based on the potential pathogenic mechanism they target.